A Technical, Economic, and Environmental Performance of Grid-Connected Hybrid (Photovoltaic-Wind) Power System in Algeria - Djohra Saheb-Koussa; Mustapha Koussa; Nourredine Said (The Scientific World Journal)
This paper studies the technical, economic, and environmental analysis of wind and photovoltaic power systems connected to a conventional grid. The main interest in such systems is on-site consumption of the produced energy, system hybridization, pooling of resources, and contribution to the environment protection. To ensure a better management of system energy, models have been used for determining the power that the constituting subsystems can deliver under specific weather conditions. Simulation is performed using MATLAB-SIMULINK. While, the economic and environmental study is performed using HOMER software. From an economic point of view, this allows to compare the financial constraints on each part of the system for the case of Adrar site which is located to the northern part of the south of Algeria. It also permits to optimally size and select the system presenting the best features on the basis of two parameters, that is, cost and effectiveness. From an environmental point of view, this study allows highlighting the role of renewable energy in reducing gas emissions related to greenhouse effects. In addition, through a set of sensitivity analysis, it is found that the wind speed has more effects on the environmental and economic performances of grid-connected hybrid (photovoltaic-wind) power systems.